2021
DOI: 10.1136/oemed-2021-107461
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 antibody seroprevalence among firefighters in Orange County, California

Abstract: ObjectivesWe conducted serological SARS-CoV-2 antibody testing from October to November 2020 to estimate the SARS-CoV-2 seroprevalence among firefighters/paramedics in Orange County (OC), California.MethodsOC firefighters employed at the time of the surveillance activity were invited to participate in a voluntary survey that collected demographic, occupational and previous COVID-19 testing data, and a SARS-CoV-2 immunoglobulin (Ig)G antibody blood test. We collected venous blood samples using mobile phlebotomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…This area of high risk observed in our study consists of minority communities who may also reside in crowded neighborhoods, may not be able to physically distance, and have other comorbidities that may worsen their COVID-19 prognosis [ 35 ]. An occupational study on seroprevalence among firefighters also identified a higher proportion of Hispanic firefighters who were reluctant to participate in disease surveillance activities, suggesting there may be hesitancy towards public health activities [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This area of high risk observed in our study consists of minority communities who may also reside in crowded neighborhoods, may not be able to physically distance, and have other comorbidities that may worsen their COVID-19 prognosis [ 35 ]. An occupational study on seroprevalence among firefighters also identified a higher proportion of Hispanic firefighters who were reluctant to participate in disease surveillance activities, suggesting there may be hesitancy towards public health activities [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of infection predictors examined risk factors within specific settings and sub-populations, including face coverings and distancing among occupants of a military ship [210], ethnic composition and exposure risk factors in employees of industrial facilities [222,241,265,270,282], including one study that compared the incidence before and after mitigation strategies such as masking and barriers in a meat processing facility [265], shelter residence status among people experiencing homelessness [271,302], screening strategies and staffing levels in skilled nursing facilities [227,228,243,247,272], housing type and athletic participation among college students [234,300], and community exposures and symptomatic contacts in children [242,261,264,267,277,280,283,294,295,306]. Several studies use seroprevalence surveys or administrative data to examine infection risk factors among healthcare workers and first responders [224,233,239,257,259,274,289,299]. One analytic study evaluated serial testing of healthcare workers in a skilled nursing facility [272].…”
Section: Plos Onementioning
confidence: 99%